Modern teaching of physical education - Qureshi, M.U (New Delhi, 2004)
Education is a vast discipline and Teachers' Training is a vital part of it. The responsibilities of the educationists and educators are focused on the task of providing better training to the future teachers for their better learning and proper development. Needless to say that this responsibility can only be exercised, if the trainers are equipped with the required knowledge of the subject concerned. That's why it becomes essential for making adequate provisions for each course to the student-teachers or teacher trainees. The present series is designed for providing a solid workable base for all course-papers. It has been prepared strictly according to the syllabus of the B.Ed. class, prescribed by the UGC for different universities.
Keywords: Physical education- study and teaching